Alcohol consumption, life history and extinction risk among Raute hunter–gatherers from Nepal - Inez Derkx; Gina Menn; Sudarshan Subedi; Nagendra Upadhyaya; Prajwal Rajbhandari; Anita Gyawali; Ruth Mace; Jaume Bertranpetit; Lucio Vinicius; Andrea Bamberg Migliano (Evolutionary Human Sciences)
Hunter–gatherer populations underwent a mass extinction in the Neolithic, and in present times face challenges such as explicit sedentarisation policies. An exception is in Nepal, where the nomadic Raute people receive monthly governmental individual payments. One consequence of the money transfers has been a significant increase in alcohol consumption, with nearly all individuals drinking industrially produced alcohol. Here we investigate the Raute demography based on a full census of 144 individuals. We show that the Raute exhibit the short life expectancies typical of other hunter–gatherer populations from Africa, Asia and America. Bayesian survival trajectory analysis demonstrated that heavy drinking by either parent substantially reduces offspring survival to age 15. Bayesian regressions revealed a significant effect of heavy drinking on maternal fertility by decreasing the number of living children and reducing the proportion of live children at the end of maternal reproductive life. Although the absence of data prior to monetary support precludes a direct assessment of long-term demographic trends, relatively stable population sizes over the last decades and a fertility rate close to the replacement rate rule out an imminent population crash. Further studies are required to elucidate the Rautes’ origins and relationship with other nomadic people in the region.